Association between weekend warriors and MASLD—a cross-sectional study of the NHANES database 2017–2020 - Su, Bo Yang; Wang, Song; Liu, Tie Jun; Leng, Yan; Liu, Zhi Yuan; Liu, Lu; Xiong, Zhuang (Frontiers in Medicine, 2025)
BackgroundThe prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) continues to rise each year, posing a significant threat to people in their physical and mental health, as well as imposing a considerable economic burden on healthcare systems. Furthermore, physical activity (PA) is recognized as one of the effective strategies for the prevention of MASLD. However, the epidemiological evidence on the association between weekend warriors’ (WWs) exercise modes and MASLD is inconsistent. The primary objective of this study was to further investigate the association between weekend warriors and the prevalence of MASLD using the NHANES database.MethodsThis study included a total of 4,671 participants from the National Health and Nutrition Examination Survey (NHANES) database. PA questionnaires were used to assess participants’ PA patterns, while vibration-controlled transient elastography (VECT) was used to assess the degree of hepatic steatosis, and other data were used to diagnose MASLD. Three distinct models were developed to compare the associations between various exercise patterns and the prevalence of MASLD through logistic regression, and to compare the differences between RA and WWs in the prevalence of MASLD.ResultsThere is a clear link between the involvement of WWs or RA participants and the lower prevalence of MASLD. In the final adjusted model, participants with a weekend warrior physical activity pattern (odds ratio [OR]: 0.511, 95% confidence interval [CI]: 0.373–0.701, p = 0.00.6) and those in the regular activity population (OR: 0.621, 95% CI: 0.512–0.754, p: 0.00.3) showed significantly lower risk ratios compared to individuals in the inactive and under-exercised populations, and this was statistically significant. Using the regular activity population as a reference, the risk of prevalence of MASLD in the weekend warrior group (OR: 0.857, 95% CI: 0.548–1.339, p: 0.516) indicates that no statistically meaningful disparity was observed between the two groups.ConclusionIn summary, our results demonstrate a significant correlation between WWs’ activity patterns and their risk of MASLD, and they indicate that these patterns can improve MASLD with benefits comparable to those of RA. This provides additional options for individuals with MASLD who are unable to meet the recommended criteria in the exercise guidelines, along with treatment options for clinicians.